Comparing COVID-19 severity in patients hospitalized for community-associated Delta, BA.1 and BA.4/5 variant infection - Sočan, Maja; Mrzel, Maja; Prosenc, Katarina; Korva, Miša; Avšič-Županc, Tatjana; Poljak, Mario; Lunar, Maja M.; Zupanič, Tina (Frontiers in Public Health, 2024)
Background: Despite decreasing COVID-19 disease severity during the Omicron waves, a proportion of patients still require hospitalization and intensive care.Objective: To compare demographic characteristics, comorbidities, vaccination status, and previous infections in patients hospitalized for community-associated COVID-19 (CAC) in predominantly Delta, Omicron BA.1 and BA.4/5 SARS-CoV-2 waves. Methods: Data were extracted from three national databases -the National COVID-19 Database, National Vaccination Registry and National Registry of Hospitalizations.Results: Among the hospitalized CAC patients analyzed in this study, 5,512 were infected with Delta, 1,120 with Omicron BA.1, and 1,143 with the Omicron BA.4/5 variant. The age and sex structure changed from Delta to BA.4/5, with the proportion of women (9.5 % increase), children and adolescents (10.4 % increase), and octa-and nonagenarians increasing significantly (24.5 % increase). Significantly more patients had comorbidities (measured by the Charlson Comorbidity Index), 30.3 % in Delta and 43 % in BA.4/5 period. The need for non-invasive ventilatory support (NiVS), ICU admission, mechanical ventilation (MV), and in-hospital mortality (IHM) decreased from Delta to Omicron BA.4/5 period for 12.6 %, 13.5 %, 11.5 % and 6.3 %, respectively. Multivariate analysis revealed significantly lower odds for ICU admission (OR 0.68, CI 0.54-0.84, p<0.001) and IHM (OR 0.74, CI 0.58-0.93, p=0.011) during the Delta period in patients who had Pripombe dodal [MS1]: The title has been changed according to the suggestion of Reviewer 2 first and finally, the title has been changed according to the Editor suggestion been fully vaccinated or boosted with a COVID-19 vaccine within the previous six months. In the BA.1 variant period, patients who had less than six months elapsed between the last vaccine dose and SARS-CoV-2 positivity had lower odds for MV (OR 0.38, CI 0.18-0.72, p=0.005) and IHM (OR 0.56, CI 0.37-0.83, p=0.005), but not for NIVS or ICU admission.The likelihood of developing severe CAC in hospitalized patients was higher in those with the Delta and Omicron BA.1 variant compared to BA.4/5.